El enfoque invisible : perspectivas feministas en la enseñanza del derecho del trabajo - Lobato, Julieta (2019)
The aim of this work is to carry out an exploratory approach on the ways in which Labour Law is taught in the Faculty of Law of the University of Buenos Aires, from a feminist perspective. Our central thesis holds that gender perspective is the invisible focus in the processes of legal-labour knowledge transfer, since the discipline is presented as if it were gender-neutral. We will develop our argument in four main sections. In the first place, we will contextualize the teaching-learning of Labour Law processes (I). Then, we will review the main bibliography on feminism that links gender and work (II). Thirdly, we will analyze the chairs programs and the main manuals corresponding to the subject "Elements of Labour Law" (III). Finally, we will outline some proposals (IV) in order to delineate the final conclusions about the challenges regarding the teaching of Labour Law with a gender perspective.